Export volume trends and the conservation status of commonly targeted ornamental fishes from Malawi - Amulike Victor Msukwa; Wilson Lazaro Jere (Oryx)
The export of ornamental fishes from Malawi has received limited attention regarding its sustainability or the conservation status of any threatened species involved in this trade. To identify any species that require specific management actions, we used a negative binomial regression model to examine the relationship between the number of exported fish and year of export, adjusted for fish prices and the number of fish exporters. We also examined the correlation between export volume trends and the conservation status of fish species. We identified three groups of fish species based on their export volume trends: species with no trends, with decreasing trends and with increasing trends. There was no significant correlation between export volume trends and the conservation status of fish species. The export volume trends of individual species appear to be related to the number of exporters, price and, potentially, anthropogenic factors affecting fish populations. Based on our findings we recommend the inclusion of ornamental fishery management issues in a revised Fisheries and Aquaculture Policy. This should include strategies to control overexploitation of species with declining export volume trends, and conservation of threatened species and a ban on their export. We recommend further research to establish the population status of the exploited fish species and to identify any other factors linked to the volume trends of ornamental fish exports.